Access to academic libraries: an indicator of openness? - Wilson, Katie; Neylon, Cameron; Montgomery, Lucy; Huang, Chun-Kai Karl (Information Research, 2019)
Introduction. Open access to digital research output is increasing, but academic library policies can place restrictions on public access to libraries. This paper reports on a preliminary study to investigate the correlation between academic library access policies and institutional positions of openness to knowledge. Method. This primarily qualitative study used document and data analysis to examine the content of library access or use policies of twelve academic institutions in eight countries. The outcomes were statistically correlated with institutional open access publication policies and practices. Analysis. We used an automated search tool together with manual searching to retrieve Web-based library access policies, then categorised and counted the levels and conditions of public access. We compared scores for institutional library access feature with open access features and percentages of open access publications. Results. Academic library policies may suggest open public access but multi-layered user categories, privileges and fees charged can inhibit such access, with disparities in openness emerging between library policies and institutional open access policies. Conclusion. As open access publishing options and mandates expand, physical entry and access to print and electronic resources in academic libraries is contracting. This conflicts with global library and information commitments to open access to knowledge.